Here's the question you clicked on:
ohhailayne
3/m-4+1/3(m-4)=6/m Help! Solving rational expressions
\[\frac{ 3 }{ m }-4+\frac{ 1 }{ 3(m-4) }=\frac{ 6 }{ m }\]is it like this?
yes! @Linyu I just need to know how to do it, my book doesn't give an example for ones like this
you need to convert the denominators to the same form\[\frac{ a }{ b }+\frac{ c }{ d }=\frac{ ad }{ bd }+\frac{ cb }{ bd }\]
@ohhailayne are you with me?
hmm... not sure if you catch up. Okay I'll try to solve this one step by step so you could understand
I think I've got it? @Linyu
\[\frac{ 3 }{ m }-\frac{ 4 }{ 1 }+\frac{ 1 }{ 3(m-4) }=\frac{ 6 }{ m }\] convert the denominator into 3m(m-4) we have\[\frac{ 3(m-4) }{ 3(m-4) }\times \frac{ 3 }{ m }-\frac{ 3m(m-4) }{ 3m(m-4) }\times \frac{ 4 }{ 1 }+\frac{ m }{ m }\frac{ 1 }{ 3(m-4) }=\frac{ 3(m-4) }{ 3(m-4) }\times \frac{ 6 }{ m }\]
now all the denominators are the same 3m(m-4) so feel free to cancel them out. And you'll get\[3(m-4)\times3-3m(m-4)\times4+m=3(m-4)\times6\]
the problem should be \[\frac{ 3 }{ m-4 }+\frac{ 1 }{ 3(m-4) }=\frac{ 6 }{m? }\]
Oh! that will be better to solve
yes! so I think the answer is 10/m-4 @Linyu
3m(3)+m=3(m-4)(6) 9m+m=18m-72 10m=18m-72 0=8m-72 72=8m m=72/8 m=9
I hope you understand. Not only know the answer.